2019
DOI: 10.31539/jka.v1i1.747
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pendidikan Kesehatan Media Video dan Poster terhadap Pengetahuan dan Sikap Anak dalam Pencegahan Penyakit Diare

Abstract: This study aims to determine the effect of health education using video and poster media on the knowledge and attitudes of fourth grade SDN 65 Seluma children in preventing diarrhea. This type of research is a quantitative study with a quasi-experimental approach using a two group pre and post test design. The results showed that the average score of children's knowledge in the video media group before the intervention was 68.00, after the intervention was 86.67, the child's attitude before the intervention wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 0 publications
2
5
0
9
Order By: Relevance
“…Health messages given in the form of posters will certainly be more interesting because posters are loaded with visual images, thus involve one's sense of sight more, what a person sees only involves 30% of the sense of sight, the more exerting the senses when receiving a health message, the higher the level of delivery of the health message to someone in catching the message or socialization material will be more effective (Adriansyah & Rahmah, 2021). The use of media that involves many senses will further increase understanding of information, thus the use of poster media is considered more effective and attractive for respondents to achieve the goal of delivering health messages (J, Oktavidiati and Astuti, 2019). This research was in line with the research on the effectiveness of poster media which showed the differences in the level of knowledge before and after being given poster media to respondents.…”
Section: Methodssupporting
confidence: 77%
See 1 more Smart Citation
“…Health messages given in the form of posters will certainly be more interesting because posters are loaded with visual images, thus involve one's sense of sight more, what a person sees only involves 30% of the sense of sight, the more exerting the senses when receiving a health message, the higher the level of delivery of the health message to someone in catching the message or socialization material will be more effective (Adriansyah & Rahmah, 2021). The use of media that involves many senses will further increase understanding of information, thus the use of poster media is considered more effective and attractive for respondents to achieve the goal of delivering health messages (J, Oktavidiati and Astuti, 2019). This research was in line with the research on the effectiveness of poster media which showed the differences in the level of knowledge before and after being given poster media to respondents.…”
Section: Methodssupporting
confidence: 77%
“…A poster is a presentation of a clear, striking, and attractive visual combination with the intention of attracting people's attention to something or influencing someone to act (Kurniawan et al, 2020). The form of a simple poster, presenting one idea and achieving one main goal, colorful, has a special slogan, as well as clear and varied writing can make it easier and faster for the audience to catch the message presented (J, Okatvidanti and Astuti et al, 2019). oster media can also facilitate faster and more efficient delivery of ideas, supported by the rapidly growing social media (Qomarrullah, R; Siahaan, J; Sawir, M; S Wulandari, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Bentuk poster yang sederhana, menyajikan satu ide dan untuk mencapai satu tujuan pokok, berwarna, memiliki slogan khusus, serta tulisan yang jelas dan bervariasi dapat mempermudah dan mempercepat audiens menangkap pesan yang disajikan. (Harsismanto, Oktavidiati, & Astuti, 2019). Se l a i n po st e r, m edia edukasi yang juga sering digunakan untuk mengedukasi masyarakat adalah video.…”
Section: Pendahuluanunclassified
“…9-16) Available Online at https://ejournal2.undip.ac.id/index.php/hnhs Layalia Azka Rahmatina, dkk., Evaluasi Program Edukasi dengan Video dan Poster.... pp yang diterima oleh individu tersebut. (Harsismanto et al, 2019). Perubahan perilaku yang dialami masyarakat dipengaruhi karena adanya peningkatan pengetahuan mengenai manfaat dan cara merubah perilakunya (Buana, 2020).…”
Section: Journal Of Holistic Nursing and Health Scienceunclassified
“…Keberadaan gambar dan desain visual yang menarik pada poster meningkatkan minat untuk membaca informasi yang ada di dalamnya (Rahmawati et al, 2020;Ulya & Iskandar, 2017). Penggunaan media poster pada pemberian informasi Kesehatan efektif dan berpengaruh signifikan dalam meningkatkan pengetahuan dan sikap anak dalam pencegahan penyakit infeksius (J et al, 2019;Ulya & Iskandar, 2017). Sosialisasi melalui poster seperti pada gambar 7 diharapkan dapat memberikan informasi mengenai PHBS pada warga panti dan bisa digunakan sebagai pengingat dalam kehidupan sehari-hari.…”
Section: Gambar 4 Pentingnya Materi Yang Disampaikanunclassified